Pengaruh Kepemilikan Institusional, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Tax Avoidance - Tarigan, Rizky Sovri; Fitria Eka Ningsih (EkoPreneur, 2025)
Taxes are a significant source of revenue for a country, but for individualsandcompanies, they are a burden because they reduce their income, especially sincethey receive no direct compensation for paying them. This is why individuals andcompanies seek to avoid taxes. What influences tax avoidance in a company?Whatinfluences tax avoidance in a company. This study aims to examine and determinethe effect of institutional ownership, sales growth, and company size on taxavoidance. The independent variables in this study are company size, sales growth,and institutional ownership, while the dependent variable is tax avoidance (ETR).This study uses companies in the Consumer Non-Cyclical sector, food and beveragesub-sector, listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period.The method used in this study ispurposive sampling, a sampling technique withcertain considerations. The type of research used is quantitative, associative,namely research conducted to determine the relationship between two or morevariables regarding the condition of the company using quantitative and qualitativedata measured in a numeric scale or in the form of numbers. 11 companies wereselected to be used as research samples with 5 years of observation, so that the totalsample in this study was 55 samples. The data analysis technique used in this studyis panel data regression analysis using eviews 12 software. Based on the results ofthe study, it shows that simultaneously Institutional Ownership, Sales Growth andCompany Size have an effect on Tax Avoidance, partially Institutional Ownershiphas no effect on Tax Avoidance, Sales Growth has no effect on Tax Avoidance, andCompany Size has an effect on Tax Avoidance. Keywords: Institutional Ownership, Sales Growth, Company Size, Tax Avoidance